Decreasing Failure in Programming Subject with Augmented Reality Tool - Del Bosque, Laura; Martinez, Raquel; Torres, Jose Luis (Procedia computer science, 2015)
University education, it has considered using technology application to motivate and increase performance and student achievement in their learning units. As our knowledge, the academic world is excluded from these initiatives; the use of emerging technology in education has begun introducing it of Augmented Reality in some of their disciplines. However, the knowledge and application of this technology in teaching are minimal. Augmented reality and game theory promote research among students. This methodology has been used before in order to capture the interest, attention, and learning when the students are motivated [1]. This article shows mainly as the failure rate has decreased by 50% in the subject of structured programming, thanks to the learning activities undertaken with an augmented reality tool based on the principles of game theory. This application has supported the performance and motivation among students and has influenced to continue with the rest of the course and they may continue their studies by not failing their school year and their career.